PI‐RADS in Predicting csPCa: A Comparison Between Academic and Nonacademic Centers - Orsini, Angelo; Ferretti, Simone; Porreca, Annamaria; Castellan, Pietro; Litterio, Giulio; Ciavarella, Davide; De Palma, Antonio; Berardinelli, Francesco; Pizzi, Andrea D.; D'Angelo, Emanuela; Nicola, Marta; Schips, Luigi; et al. (The Prostate, 2025)
ABSTRACT Introduction The introduction of multiparametric prostate magnetic resonance imaging (mpMRI) has revolutionized prostate cancer (PCa) diagnosis, enhancing the localization of clinically significant prostate cancer (csPCa) and guiding targeted biopsies. However, significant disparities in the execution, interpretation, and reporting of prostate MRI examinations across centers necessitate greater standardization and accuracy. This study compares the diagnostic efficacy of mpMRI from academic and nonacademic centers in detecting csPCa and identifies factors associated with csPCa detection. Materials and Methods Between July 2018 and October 2023, we prospectively followed 810 men at SS. Annunziata Hospital of Chieti who underwent MRI/US fusion biopsies due to elevated prostate‐specific antigen (PSA) and/or abnormal digital rectal examination (DRE). Patients with mpMRI‐documented suspicious lesions classified as PI‐RADS ≥ 3 were included. Patients were divided into two groups based on the source of their mpMRI (academic or nonacademic centers). All biopsies were conducted using the MRI/US fusion technique. Clinical, mpMRI, and pathological data were collected and analyzed. Statistical analyses were performed using R software. Results The cohort included 354 patients from academic centers and 456 from nonacademic centers. There were no significant differences in patient demographics, such as age and PSA levels, between the groups. Patients at academic centers were more likely to receive a higher number of elevated PI‐RADS scores compared to those at nonacademic centers (PI‐RADS > 3: 72.6% vs. 62.3%, p = 0.003). Histopathological analysis revealed no significant differences in the ISUP grade distribution between groups. Increased age, PSA levels, and positive DRE were significantly associated with higher odds of detecting csPCa. Median PSA density was significantly higher in patients with csPCa compared to those without csPCa (0.14 vs. 0.11 ng/mL/cm³, p < 0.001). Academic centers exhibited a higher odds ratio for csPCa detection in patients with PI‐RADS scores > 3 compared to nonacademic centers. Conclusion Our study highlights significant variability in PI‐RADS score assignments between academic and nonacademic centers, affecting csPCa detection rates. This variability underscores the need for greater standardization in PI‐RADS scoring to reduce disparities and improve diagnostic uniformity across centers.